A Study of Neem Seed Husk Ash as Partial Replacement for Cement in Concrete - Raheem, Akeem Ayinde; Olatunde Ibiwoye, Emmanuel (International Journal of Sustainable Construction Engineering and Technology, 2018)
The production of neem products from neem tree generates large quantity of waste annually. There is need to reduce environmental pollution resulting from neem seed covering. Therefore, the use of Neem Seed Husk Ash (NSHA) as partial substitution for cement in concrete was investigated. Neem seed husk was obtained from Bishop Smith Memorial College, Ilorin, Nigeria; sun â€“ dried for 3 days and then calcined at 650o C. The calcined neem seed husk was ground and sieved using 200 Î¼m sieve to obtain NSHA. Pozzolanicity test was conducted on NSHA to determine its chemical composition. Concrete was produced with 5, 10, 15, 20 and 25% by weight of NSHA substitution for ordinary Portland cement. Workability tests (slump and compacting factor) were performed on fresh concrete while compressive strength test was conducted on 150 mm cubes at ages 3, 7, 14, 21, 28, 56, 90 and 180 days for the hardened concrete. NSHA mainly comprises Al2O3, SiO2 and Fe2O3 with a combined percentage of 75.35%.Â The slump and compacting factors of NSHA concrete ranged from 5.50 mm to 10.00 mm and 0.91 to 0.95, respectively. The compressive strength at 180 days decreased from 26.9 N/mm2 to 19.4 N/mm2 as the NSHA content increased from 5% to 25%. Only 5% NSHA substitution is adequate to enjoy maximum benefit of strength gain.